Characterisation of oleoresins extracted from tomato waste by liquid and supercritical carbon dioxide. (13th May 2020) - Romano, Raffaele; Aiello, Alessandra; Pizzolongo, Fabiana; Rispoli, Andrea; De Luca, Lucia; Masi, Paolo
Abstract: Tomato waste is characterised by high amounts of bioactive compounds, such as carotenoids, polyphenols and essential fatty acids. In this work, oleoresins were produced from tomato waste (skins + seeds) and skins using carbon dioxide under liquid and supercritical conditions. The use of ethanol as a co‐solvent was also evaluated. Compositions of the oleoresins were analysed and compared to oleoresin obtained by means of an organic solvent, which was used as the control. Oleoresin extraction from the waste by liquid and supercritical CO2 provided the highest yields (12.5%–12.9%). The extracts obtained from the skins with supercritical CO2 without ethanol had the highest content of α‐ and γ‐tocopherols (80 and 575 mg/100 g oleoresin, respectively), while lycopene and β‐carotene were found at 205 and 75 mg/100 g oleoresin, respectively. The highest quantity of polyphenols (9305 mg GAE/100 g oleoresin) was found in the oleoresin extracted from skin by supercritical CO2 with ethanol. All oleoresins were characterised by a high antioxidant activity, which improved with the synergy of carotenoids, tocopherols and polyphenols. Abstract : Oleoresins extracted from tomato waste by liquid and supercritical carbon dioxide.